2007
DOI: 10.1038/emm.2007.89
|View full text |Cite
|
Sign up to set email alerts
|

ATP released from β‐amyloid-stimulated microglia induces reactive oxygen species production in an autocrine fashion

Abstract: Present study demonstrated that fibrillar β-amyloid peptide (fAβ 1-42 ) induced ATP release, which in turn activated NADPH oxidase via the P2X 7 receptor (P2X 7 R). Reactive oxygen species (ROS) production in fAβ1-42-treated microglia appeared to require Ca 2+ influx from extracellular sources, because ROS generation was abolished to control levels in the absence of extracellular Ca 2+. Considering previous observation of superoxide generation by Ca 2+ influx through P2X 7 R in microglia, we hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 18 publications
3
72
0
Order By: Relevance
“…Another critical issue remaining to be further investigated is the molecular targeting of rottlerin to inhibit mitochondrial O 2 -production. The Nox family of NADPH oxidase has been implicated as a major source of ROS (Lambeth, 2004;Kim et al, 2005Kim et al, , 2007a. To test whether the ROS generated by NADPH oxidase play a role, we pretreated L929 cells with diphenylene iodonium (DPI), a well-established NADPH oxidase inhibitor in the presence of TNF, and measured mitochondrial O 2 -production.…”
Section: Rottlerin Suppresses Tnf-induced Nox1 Activation In Murine Fmentioning
confidence: 99%
“…Another critical issue remaining to be further investigated is the molecular targeting of rottlerin to inhibit mitochondrial O 2 -production. The Nox family of NADPH oxidase has been implicated as a major source of ROS (Lambeth, 2004;Kim et al, 2005Kim et al, , 2007a. To test whether the ROS generated by NADPH oxidase play a role, we pretreated L929 cells with diphenylene iodonium (DPI), a well-established NADPH oxidase inhibitor in the presence of TNF, and measured mitochondrial O 2 -production.…”
Section: Rottlerin Suppresses Tnf-induced Nox1 Activation In Murine Fmentioning
confidence: 99%
“…In recent years the P2X 7 receptor has attracted increasing interest as a possible player in neuroinflammation (17)(18)(19)(20)(21). More recently it has been shown that stimulation of microglia P2X 7 receptor causes neuronal damage via release of activated oxygen species (10), that blockade of this receptor attenuates inflammatory brain damage caused by intrastriatal injection of bacterial endotoxin (22), and that A␤ may cause ATP release from microglia (23). This observation put ATP and P2 receptors at the heart of research in neurodegenerative diseases (24).…”
mentioning
confidence: 99%
“…The observation that Aβ may cause ATP release from microglia, and that P2X7 receptor is an obligate participant in microglia activation by Aβ, put the role of ATP and P2 receptors as a key event in neurodegeneration [42,63]. Recent data demonstrated that in vivo inhibition of P2X7 receptors significantly reduces the amyloid plaques formation in brain hippocampal structures through activation of α-secretase activity [51].…”
Section: Discussionmentioning
confidence: 99%
“…Aging of the peptides was induced by shaking the diluted solution (50 μM) at 1000 rpm overnight at 37°C. The cells were treated after synchronization at a final concentration of 0.5 μM of Aβ 42 . In selected experiments, after measurement of basal Ca 2+ levels, cells were treated either with a sarco/endoplasmic reticulum Ca 2+ ATPase (SERCA) inhibitor (Thapsigargin; 10 nM), or with an agonist (ATP; 1 mM) of purinergic P2X7 receptors.…”
Section: Preparation Of Aβ Species and Cell Treatmentmentioning
confidence: 99%
See 1 more Smart Citation